2022
DOI: 10.1111/jocd.14799
|View full text |Cite
|
Sign up to set email alerts
|

30% supramolecular salicylic acid peels effectively treats acne vulgaris and reduces facial sebum

Abstract: Background Acne is a chronic inflammatory skin disease with high incidence and recurrence. Aim To study the efficacy of 30% supramolecular salicylic acid (SSA) in the treatment of acne, especially its effect on facial sebum secretion and the skin barrier. Methods Chemical peeling treatment with SSA using self‐contrast was performed every 2 weeks for a total of four treatments in 25 patients. VISIA photographs and skin parameter measurements were recorded at every treatment, with a 2‐week follow‐up after the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Large pores are common skin problems associated with excessive sebum secretion [41]. Salicylic acid can dissolve excess oil secreted by the skin and is often used to control sebum secretion [42,43]. Its mechanism of regulating skin oil secretion is downregulating SREBP-1 and NF-κB pathways of SEB-1 sebocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Large pores are common skin problems associated with excessive sebum secretion [41]. Salicylic acid can dissolve excess oil secreted by the skin and is often used to control sebum secretion [42,43]. Its mechanism of regulating skin oil secretion is downregulating SREBP-1 and NF-κB pathways of SEB-1 sebocytes.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Clinical investigations have already revealed that transepidermal water loss (TEWL), a measure of skin barrier impairment, either decreased or showed no statistical difference after 30% supramolecular SA chemical peeling 4 times with 2-week intervals. 12 , 24 However, there is little research on the safety evaluation of long-term consecutive SA application with relatively low concentration and its impacts on the epidermal barrier. In our study, we discovered that following topical SA treatment with doses ranging from 0.5% to 5% for 14 days and 28 days, there were no prominent alterations in the gross appearance of murine dorsal skin.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that 30% SSA was a safe and effective treatment for AV and could reduce sebum production [ 19 ]. However, very few studies have explored the role of SSA in the treatment of skin microbiota and inflammation in patients with moderate-to-severe AV.…”
Section: Introductionmentioning
confidence: 99%